Intensity of blue LED light: A potential stimulus for biomass and lipid content in fresh water microalgae Chlorella vulgaris - Atta, Madiha; Idris, Ani; Bukhari, Ataullah; Wahidin, Suzana (Bioresource technology, 2013)
•Blue LED intensity and photoperiods influence Chlorella vulgaris growth rates.•Light intensities used; 100, 200 and 300μmolm−2s−1 at three photoperiod cycles.•Growth was maximum at blue LED of 200μmolm−2s−1 and photoperiod of 12:12h L:D.•C. vulgaris grows faster in blue LED compared to white fluorescent light.•Highest growth rate corresponds to highest lipid content of C. vulgaris. Light quality and the intensity are key factors which render microalgae as a potential source of biodiesel. In this study the effects of various intensities of blue light and its photoperiods on the growth and lipid content of Chlorella vulgaris were investigated by using LED (Light Emitting Diode) in batch culture. C. vulgaris was grown for 13days at three different light intensities (100, 200 and 300μmolm−2s−1). Effect of three different light and dark regimes (12:12, 16:08 and 24:00h Light:Dark) were investigated for each light intensity at 25°C culture temperature. Maximum lipid content (23.5%) was obtained due to high efficiency and deep penetration of 200μmolm−2s−1 of blue light (12:12 L:D) with improved specific growth (1.26d−1) within reduced cultivation time of 8days. White light could produce 20.9% lipid content in 10days at 16:08h L:D.